O sistema jurídico internacional e o terrorismo - Donato, Priscilla Bigotte (2010)
Terrorism fighting has become a challenge to the recent International Community. The means and the techniques used by terrorists have become more evolved, organized and deadly than ever. Fighting terrorism using their same weapons does not solve the problem. It is imperative that international legal system can provide support for combating terrorism, defining the situations that involve the terrorists allowing its punishment